Astronomy - Fitpatrick, Jane (South Yarra Vic, Macmillan, 2012)
Heroes of Australian Science: Astronomy by Jane Fitzpatrick explores the groundbreaking contributions of Australian astronomers and scientists in the field of astronomy. The book highlights the achievements of individuals who have shaped the understanding of the universe through their research and discoveries. It delves into the stories of these "heroes," focusing on their scientific journeys, challenges, and the impact of their work both in Australia and globally.